Men and Masculinities in Pandemic: Illness Narratives and Social Isolation Experiences of Men Diagnosed with COVID-19 in Turkey - Çarpar, Mehmet Can (Border Crossing, 2022)
This qualitative study aims to understand the illness narratives and social isolation experiences of men living in Turkey to examine the relationship between traditional masculinity norms and the pandemic. The data were gathered through semi-structured interviews with 13 men who were diagnosed with COVID-19 and four women whose spouses were diagnosed with COVID-19. According to data, the COVID-19 pandemic has (re)showed that traditional masculinity roles can damage men’s health and make men vulnerable to diseases. In addition to these health-related outcomes of the pandemic, traditional masculinity norms have also affected men’s social lives. It is seen that the men who have grown up in a more patriarchal social environment may experience the pandemic as a kind of masculinity loss and react in a more sexist way. But, there may also be positive scenarios in the future, since it is seen that the pandemic may cause men to change positively.